2016
DOI: 10.3389/fpls.2016.01214
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Resistance to Soybean Cyst Nematode (Heterodera glycines) HG Type 2.5.7 in Wild Soybean (Glycine soja)

Abstract: Soybean cyst nematode (SCN) is the most destructive soybean pest worldwide. Host plant resistance is the most environmentally friendly and cost-effective way of mitigating SCN damage to soybeans. However, overuse of the resistant soybean [Glycine max (L.) Merr.] cultivars from limited genetic resources has resulted in SCN race shifts in many soybean-growing areas. Thus, exploration of novel sources of SCN resistance and dissection of the genetic basis are urgently needed. In this study, we screened 235 wild so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 63 publications
3
80
0
3
Order By: Relevance
“…In G. soja , the identification of superior characteristics in abiotic stress tolerance (Qi et al 2014) and biotic stress resistance (Tian and Smith 2015) suggests that G. soja harbor promising novel genetic resources in biotic and abiotic resistance/tolerance. As expected, over a dozen of G. soja accessions were identified resistant to HG type 2.5.7 (race 5) in recent studies (Kim et al 2011; Kim and Diers 2013; Zhang et al 2016b). However, no G. soja resistance showed high levels of resistance to race 1 (FI<10).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…In G. soja , the identification of superior characteristics in abiotic stress tolerance (Qi et al 2014) and biotic stress resistance (Tian and Smith 2015) suggests that G. soja harbor promising novel genetic resources in biotic and abiotic resistance/tolerance. As expected, over a dozen of G. soja accessions were identified resistant to HG type 2.5.7 (race 5) in recent studies (Kim et al 2011; Kim and Diers 2013; Zhang et al 2016b). However, no G. soja resistance showed high levels of resistance to race 1 (FI<10).…”
Section: Discussionsupporting
confidence: 74%
“…This lack of resistance might be due to the completely distinct molecular mechanisms of G. soja defending against race 5 (HG type 2.5.7) vs. race 1. Our recent study (Zhang et al (2016b) identified different SNPs and candidate genes involved in G. soja resistant to race 5 (type 2.5.7) compared to this current study on SCN race 1.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations